1970
DOI: 10.4314/ahs.v19i4.6
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of hypoglycemic effect of an extract from leaves of a plant from Tunisian pharmacopeia: artemisia campestris (asteraceae)

Abstract: Background and objectives: A lot of research has been directed towards medicinal plants which are considered as a source of multiple phytotherapic substances endowed with hypoglycemic activities that could be used to treat diabetes and its complications. Our study was carried out in Wistar rats to investigate the hypoglycemic effect of n-Butanol Fraction from Artemisia campestris leaf Methanolic Extract (BFACME).Methods: Two experimental models were used in rats: orally induced hyperglycemia (OGTT) and isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…After 12 hr fasting, all the mice were fed with glucose (2 g/kg, b.w.). The blood was collected from the tail vein at 0, 30, 60, 90, and 120 min, and blood glucose levels were monitored using a glucometer (Accu‐Chek, India) (Belgacem et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…After 12 hr fasting, all the mice were fed with glucose (2 g/kg, b.w.). The blood was collected from the tail vein at 0, 30, 60, 90, and 120 min, and blood glucose levels were monitored using a glucometer (Accu‐Chek, India) (Belgacem et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In other words, our extracts have an inhibitory effect against α-amylase and α-glucosidase in vivo, which confirmed by the fact that hydrolysis effect of these enzymes inhibited in vitro significantly by AcAE and AcEE. In orally induced hyperglycemia model, the n-butanol Fraction from Tunisian Artemisia campestris L. at the highest doses of 550 and 400 mg/kg.bw significantly reduced the postprandial hyperglycemic peak compared to control [20]. Two other Moroccan Asteraceae species (Bubonium imbricatum Cav.…”
Section: Discussionmentioning
confidence: 93%
“…Different pharmacological studies showed that Artemisia campestris L. has antibacterial [13], antitumor [14], anti-inflammatory [15], antiplatelet [16], antispasmodic [17], antidiarrheal [18], and anti-ulcer activities [19]. Belgacem et al [20] reported that Artemisia campestris L. has a hypoglycemic impact, however no information was provided on the mechanism of action responsible for this effect. Chronic hyperglycemia induces the production of extreme amounts of reactive oxygen species in the tissues and this progression can lead to sever organ damage.…”
Section: Introductionmentioning
confidence: 99%